2013
DOI: 10.1002/mds.25625
|View full text |Cite
|
Sign up to set email alerts
|

Rotigotine polyoxazoline conjugate SER‐214 provides robust and sustained antiparkinsonian benefit

Abstract: Currently available dopaminergic drugs such as levodopa and dopamine (DA) receptor agonists impart considerable improvement in Parkinson's disease (PD) motor symptoms but often lead to significant motor complications including “wearing‐off” and dyskinesia. Such complications are believed to stem from the pulsatile nature of dopaminergic stimulation with these agents. Continuous dopaminergic drug delivery using polyoxazoline (POZ) polymer conjugation may improve motor symptoms, while avoiding development of sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 32 publications
0
30
1
Order By: Relevance
“…10 to 20 times higher drug concentration in injectable formulations than the clinical alternatives of Taxol, Genexol-PM, and Abraxane. Poly(2-oxazoline)s (POx) in general have received increasing attention recently as alternatives to polyethylene glycol based systems [30-34] and first-in-man studies are expected to commence in 2015 [35,36]. Here, we combine the possibilities of our POx-based drug delivery platform for safe and efficient drug formulation and delivery with the advantages of 3 rd -generation taxoids, which can overcome multidrug resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…10 to 20 times higher drug concentration in injectable formulations than the clinical alternatives of Taxol, Genexol-PM, and Abraxane. Poly(2-oxazoline)s (POx) in general have received increasing attention recently as alternatives to polyethylene glycol based systems [30-34] and first-in-man studies are expected to commence in 2015 [35,36]. Here, we combine the possibilities of our POx-based drug delivery platform for safe and efficient drug formulation and delivery with the advantages of 3 rd -generation taxoids, which can overcome multidrug resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…85 The use of a hydrolytically cleavable ester linker between the PAOx chain and the drug allowed for control over drug release rate. As such, sustained release of rotigotine was observed in male rats, leading to long-term anti-parkinsonian effects as well as a reduction of motor complications, which is commonly observed in therapies that cause large dopamine fluctuations.…”
Section: Applications Of Poly(2-oxazoline)s With Clickable Side Chainsmentioning
confidence: 99%
“…65 In vivo studies, using 6-hydroxydopamine (6-OHDA) lesioned rat models, showed SER-214 (slow-release conjugate) to have a prolonged RTG half-life with reduced motor complications, which was sustained over repeated dosing. 66 With these promising results, SER-214 has now Food and Drug Administration's approval to enter phase 1 study (NCT02579473) using de novo PD patients. 67 …”
Section: Non-levodopa-based Therapiesmentioning
confidence: 99%